The Relationship of Perceptions of Family Planning Acceptors and Election of Long-Term Contraceptive Methods in Sorimanaon Village - Harahap, Lena Juliana; Harahap, Lia Junita (Institute Of Computer Science (IOCS), 2024)
The family planning program is one of the government's efforts to improve the population’s quality. The strategy in contraceptive services currently being developed is to promote the use of long-term contraceptive methods. Contraceptive methods including long-term contraceptive methods are iud, implant, mow, and mop. This research is an analytical study with a cross-sectional approach with a population of 82 people and a sampling technique, namely a total population of 82 people who are family planning acceptors for 3-month injections, and analyzed using the chi-square test. Based on the results of statistical tests, it is known that p-value = 0.000 < 0.05, meaning there is a significant relationship between perception and the choice of Long-Term Contraceptive Methods (LTCM).